Comparative Study Of Livestock Appearance And Beef Cattle Breeder Income In Aek Kuo District Of North Labuhanbatu Regency - Alwinda, Tri Avianti; Tafsin, M.; A. Trisna; S. Mulatsi (Jurnal Peternakan Integratif, 2023)
Beef cattle farming in Aek Kuo District, North Labuhanbatu Regency, North Sumatra Province is traditionally managed in an intensive and semi-intensive system. This study aimed to determine differences in the appearance of cattle and the income of beef cattle breeders using intensive and semi-intensive maintenance systems. The number of respondents used in this study were 30 breederss with livestock ownership of at least two heads of beef cattle and had been running a livestock business for at least two years. The methods used are site surveys and interviews based on questionnaires. The analysis used in this study was followed by a significant partial test (T-test) assisted by the SPSS version 25 program. The results showed an increase in the intensive population rate of 42.37% and semi-intensive 24.60%, intensive calf crop of 73% and semi-intensive 40%, calving interval intensive 17.52 months and semi-intensive 20.03 months, intensive mortality 0.4 % and semi-intensive 4%. In contrast, the income of beef cattle is IDR 11,816,617.00/year/breeder, and semi-intensive IDR 4,891,733.00/year/breeder with a comparison of the R/C Ratio of an intensive system of 1.8 and a semi-intensive system of 1.5. The partial significance test (T-test) results showed that the performance and income of farmers who used intensive rearing systems had higher values ​​and were significantly different compared to farmers who used semi-intensive rearing systems